2015
DOI: 10.1111/pai.12328
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal lymphoid nodular hyperplasia in children: The relationship to food allergy

Abstract: Intestinal LNH should be considered a benign finding in children without red flags, because the symptoms are largely self-limiting. The use of mesalamine or elimination diet does not modify the clinical outcome compared to symptomatic therapy. The presence of food allergy was not predicted by allergy skin testing and was found in a minority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…Patients were followed-up 24 months. Clinical improvement was observed in all patients, without a specific effect of mesalamine or of the elimination diet compared to symptomatic treatment [57].…”
Section: Elimination Dietsmentioning
confidence: 79%
“…Patients were followed-up 24 months. Clinical improvement was observed in all patients, without a specific effect of mesalamine or of the elimination diet compared to symptomatic treatment [57].…”
Section: Elimination Dietsmentioning
confidence: 79%
“…Gurkan et al [11] reported that LNH was found 12.6% in children who underwent colonoscopy. Lucarelli et al [17] reported an increased ratio in Italian children, i.e., 36%. In previous studies, the frequency of LNH varied between 10 and 30%, with variation depending on the terminal ileum intubation, colonoscopy indications, and study design (e.g., including only isolated LNH) [10].…”
Section: Discussionmentioning
confidence: 99%
“…Lucarelli et al [17] reported a weak association between LNH and FH. They divided the isolated LNH patients into 3 groups randomly: an elimination diet group (cow’s milk, eggs, and foods positive on skin prick tests), a mesalamine group, and a symptomatic treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…Puesto que por razones éticas no se practicaron las colonoscopias de control en pacientes con mejoría clínica, no es posible establecer si existió erradicación de la hiperplasia nodular linfoide posterior al tratamiento. 55 Se carece de estudios que evalúen la administración de salicilatos por vía rectal, que pareciera ser más lógico en pacientes con afección anorrectal o colónica.…”
Section: Tratamientounclassified